2013
DOI: 10.1080/09500693.2011.577843
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Determine the Uptake of A-level Physics?

Abstract: International audienceThere has been much concern recently in the UK about the decline in the number of students studying physics beyond age 16. To investigate why this might be we used data from a national database of student qualifications and a multilevel modelling technique to investigate which factors had the greatest impact on the uptake of physics at Advanced Level (A-level) in a particular year. Each factor of interest was entered into a separate model, whilst accounting for prior attainment and gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 10 publications
2
39
0
Order By: Relevance
“…Notwithstanding such complexity, gender-related gaps tending to favour males continue to be evident, particularly in physical science and mathematics. Our analysis of the research, however, revealed few studies that interrogated female students directly or deeply about the array of influences that seem to underpin their choices about studying science at secondary school, although many have suggested that this work be undertaken (Alexander et al 2012;Gill & Bell 2013;Homer et al 2014;Wang 2013). To contribute to addressing that apparent deficit in the literature, yet grounded in the assortment of findings and potential explanations from previous research, this study directly asked female students currently enrolled in upper secondary school physics, about strong influences important to their own science education experiences, including current interests and future aspirations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notwithstanding such complexity, gender-related gaps tending to favour males continue to be evident, particularly in physical science and mathematics. Our analysis of the research, however, revealed few studies that interrogated female students directly or deeply about the array of influences that seem to underpin their choices about studying science at secondary school, although many have suggested that this work be undertaken (Alexander et al 2012;Gill & Bell 2013;Homer et al 2014;Wang 2013). To contribute to addressing that apparent deficit in the literature, yet grounded in the assortment of findings and potential explanations from previous research, this study directly asked female students currently enrolled in upper secondary school physics, about strong influences important to their own science education experiences, including current interests and future aspirations.…”
Section: Introductionmentioning
confidence: 99%
“…Gill and Bell (2013) found prior attainment and gender, mathematics qualification at age 16, and for females, attending an independent or grammar school positively impacted on the uptake of "A" level physics. The socioeconomic status of the school seemed to exert "a significant effect on the overall number of students progressing to ' A' level physics but little effect on the proportion of girls in the cohort" [our emphasis] (IOP 2013, p. 15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains difficult to isolate any single cause, however. Any effects following from students' gender or their other background characteristics, or other influences following from schools, have often been found to be relatively small when compared to other factors (Bennett et al 2013;Gill and Bell 2013;Homer et al 2014). Instead, students' intentions to study science subjects have most strongly associated with their own attitudes towards science, such as their interest in science and their perceived utility of science, together with their confidence in their own abilities (Jensen and Henriksen 2015;Mellors-Bourne et al 2011;Regan and DeWitt 2015;Tripney et al 2010;Vidal Rodeiro 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Many young people still elect to opt out of science once it is no longer compulsory (OECD, 2009). There is much documented evidence for the possible reasons for this loss of interest in science such as the association between the cost of studying and the dropout rate (Van Langen & Dekker, 2005); the relationship between school selectivity and science uptake (Smithers & Robinson, 2007); the availability of separate sciences at GCSE level (Gill, Vidal Rodeiro, & Bell, 2009); well-qualified and enthusiastic teachers (Smithers & Robinson, 2007); and opportunities to experience science-related careers (Bennett, Lubben, & Hampden-Thompson, 2013). In addition to this, a large number of studies have identified individual factors influencing decisions to take up science such as gender (Murphy & Whitelegg, 2006), perceived usefulness of the subject (Jenkins & Nelson, 2005), enjoyment (Lyons, 2006) and perceptions of their ability (Vidal Rodeiro, 2007).…”
Section: Introductionmentioning
confidence: 99%